Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.psychres.2018.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Beyond diagnosis: Mentalization and mental health from a transdiagnostic point of view in adolescents from non-clinical population

Abstract: Corresponding Author HIGHLIGHTS• Mentalization contributes to mental health beyond symptoms • Mentalization deficit is not so much associated to general psychopathology • Higher mentalization deficit is not associated to higher comorbidity • Mentalization is associated to good role, social and general functioning • Mentalization is associated to self-esteem, resiliency and well-being ABSTRACT An increasing volume of evidence suggests that mentalization (MZ) can be an important factor in the transition from men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 97 publications
1
15
1
Order By: Relevance
“…This suggests an association between mentalizing and mental health which should be applicable to all the three evaluated elements: functioning, well-being, and also symptoms. Secondly, previous studies utilizing global measures of mentalizing found no association with general psychopathology (e.g., Ballespí et al, 2018), but it was expected that investigation with a multidimensional measure of mentalizing would provide different results. Finally, albeit limited, there is evidence supporting the association between the role of mentalizing in the development of internalizing and externalizing problems (Sharp et al, 2008).…”
Section: The Lack Of Association Between Mentalization Polarities and Internalizing Or Externalizing Symptomsmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests an association between mentalizing and mental health which should be applicable to all the three evaluated elements: functioning, well-being, and also symptoms. Secondly, previous studies utilizing global measures of mentalizing found no association with general psychopathology (e.g., Ballespí et al, 2018), but it was expected that investigation with a multidimensional measure of mentalizing would provide different results. Finally, albeit limited, there is evidence supporting the association between the role of mentalizing in the development of internalizing and externalizing problems (Sharp et al, 2008).…”
Section: The Lack Of Association Between Mentalization Polarities and Internalizing Or Externalizing Symptomsmentioning
confidence: 97%
“…Further, research shows that mentalizing is non-specifically affected in the presence of psychopathology regardless the type of disorder (Sharp et al, 2008). Mentalizing problems are prominent in personality disorders, especially in borderline and antisocial personality disorder, as well as in depression, anxiety, social anxiety, trauma-related disorders, attachment disorders, eating disorders, addictions, somatoform disorders, autism, and psychosis (see Ballespí et al, 2018;Bateman and Fonagy, 2019;Luyten et al, 2020, for a review). This nonspecific association suggests that mentalizing is decreased when mental health decreases.…”
Section: Mentalization and Mental Healthmentioning
confidence: 99%
“…It is more likely that emotional selfawareness is less stable than neuroticism and can be an effective therapeutic component for improvement through psychotherapy (De Gucht, 2003). Simply because it can serve as a tool for developing the necessary psychological resilience mechanisms (Ballespí et al, 2018). In other words, based on a social-communicative approach, the perception and understanding of emotions as less stable intrapersonal traits may play a role as a moderating factor in the relationship between neuroticism and internalizing psychopathology such as depression and anxiety.…”
mentioning
confidence: 99%
“…In the current study, therefore, we considered a multidimensional approach to attention to emotion and emotional clarity, which also provides the opportunity to capture emotion-based individual differences in the development of internalizing psychopathology. It seems crucial to understand potentially effective resilience mechanisms from a transdiagnostic perspective (Ballespí et al, 2018). Given that neuroticism is a common risk factor and a central feature of internalizing psychopathology (Spiroiu, 2018;Wilkinson, 2009).…”
mentioning
confidence: 99%
“…Therefore, an individual who is able to reflect upon the mental states of the self and others can engage in complex reasoning regarding interpersonal interactions and relationships (Fonagy et al, 1991), perceive and label emotions regarding difficult life experiences, as well as to engage in a reflective process about these experiences reducing their negative impact (Fonagy, Gergely, Jurist, & Target, 2002). In turn, this ability is linked with well‐being and resilience (Ballespí, Vives, Debbané, Sharp, & Barrantes‐Vidal, 2018; Borelli et al, 2019) facilitating the relationship between an individual's internal and external world, and it is considered a protective factor against developmental problems (Katznelson, 2014). Conversely, mentalizing impairments linked with attachment deactivating and hyperactivating strategies lead to further distress and behaviours that perpetuate symptoms and complaints as well as interpersonal problems (Luyten, van Houdenhove, Lemma, Target, & Fonagy, 2012).…”
Section: Introductionmentioning
confidence: 99%